PERBEDAAN PURSED LIPS BREATHING DENGAN PURSED LIPS BREATHING DAN LATIHAN EKSTREMITAS TERHADAP KEBUGARAN PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2020 - Sabirin Berampu; Isidorus Jehaman; Raynald Ignasius Ginting; Miftahul Zannah; Sri Dayanti (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by limited air flow in the respiratory tract that is not completely reversible and is progressive. Patients with COPD tend to experience inactivity that occurs due to reduced oxygen in the tissues, resulting in decreased fitness in helping to improve fitness given Pursed lips breathing treatment and limb training. This study was to determine the difference between pursed lips breathing with pursed lips breathing and exercise extremity on fitness in patients with COPD. Method is a quantitative research with quasi experimental type using the design of two groups pre-test and post-test, has a sample of 18 respondents divided into 2 groups, the control group (Pursed Lips Breathing) and the intervention group (Pursed Lips Breathing And Extremity Exercise) with purposive sampling technique that is adjusted to the inclusion and exclusion criteria. Analysis of the data obtained using the independent sample t test showed a p-value of 0,000 which means that there are differences in Pursed Lips Breathing with Pursed Lips Breathing and Extremity Exercises Against Fitness in Patients with COPD. With a mean of 17.22 with SD 11.487 and p-value Î± <(0.002 <0.05) in the control group (Pursed Lips Breathing) and mean 65,000 with SD 11.990 and p-value Î± <(0,000 <0.05) in the group interventions (Pursed Lips Breathing and limb training). Result showed that the average difference in fitness before and after (Pursed Lips Breathing and Extremity Exercises) was greater than in the control group (Pursed Lips Breathing). Conclusion is the difference between Pursed Lips Breathing and Pursed Lips Breathing and Extremity Exercise Against Fitness in Patients with COPD